Aplicações de nanoeletrodos como sensores na Química Analítica - Pereira, Francisco Claudece; Bergamo, Erwing Paiva; Zanoni, Maria Valnice Boldrin [UNESP]; Moretto, Ligia Maria; Ugo, Paolo (Sociedade Brasileira de Química, 2006)
Nanomaterials make up an emerging area in Chemistry and in the science of materials. This area constitutes the development of methods for synthesizing nanoscopic particles of a given material used for scientific investigation. Nanomaterials have a wide range of commercial possibilities and technological applications, including their use in analytical chemistry, as well as in electronics, optics, engineering, medicine, devices for liberation of drugs, bioencapsulation, among others. This paper presents a summary about nanoelectrodes, devices built from nanoparticles, which show great potential as electrochemical tools in many different types of analysis. The purpose of this paper is to review the construction methodologies of nanoelectrodes, and to point out their successful applicability in the various fields of immune assays and other analytical procedures with quantitative purposes.
Applications of nanoelectrodes as sensors in Analytical Chemistry
Keywords: electroanalysis; nanoelectrode; polycarbonate membrane